AJARAN ALKITAB TENTANG DEDIKASI HAMBA TUHAN BERDASARKAN I KORINTUS 9:13-16 TERHADAP ETOS KERJA - Bartholomeus Diaz Nainggolan (Fakultas Filsafat Universitas Advent Indonesia, 2014)
Preaching the gospel is one of the main tasks of the believers in Jesus Christ. It clearly has been mandated by the Lord Jesus to his disciples in the Gospel of Matthew 28:19 - 20, Acts 1:8, so they went to preach the gospel to every creature, baptizing those who believe, and continue to teach gospel to them to grow in their faith in His grace. And preaching the gospel of Jesus Christ cannot be bargained good or not good condition must be submitted (II Timothy 4:2). Because the gospel is a message of joy for everyone and is universal, then there are other things more important and urgent that gives eternal life other than the gospel of Jesus Christ (John 3:16). So proclaim the Gospel is no longer affected by how many physical blessings received, but how much dedication do pastors and church activists over the response of the grace given to him freely.